'…DAS NORMALE WEIB GEHÖRT DER ZUKUNFT': EVOLUTIONISM AND THE NEW WOMAN IN LEOPOLD VON SACHER‐MASOCH, FRIEDA VON BÜLOW AND LOU ANDREAS‐SALOMÉ. (October 2014) - Saul, Nicholas; Woodford, Charlotte; Colvin, Sarah
ABSTRACT Whilst the treatment of Darwinian and other concepts of evolution in literary theory and writing by men around 1900 has recently received attention, little has been written on their influence over women writers and their theorisation of gender at this epoch. This paper addresses the impact of 'Darwinism', in particular sexual selection, on concepts of gender and writing practice in the representative women writers Bülow and Andreas‐Salomé. These are contrasted with works by Sacher‐Masoch and with Bölsche's construction of the feminine in Das Liebesleben in der Natur. It is argued that radical feminism emerged even in prominent feminist writers around 1900 in an inhibited form, and that the authority attributed to Darwinistic constructions of sexual selection was a factor in that phenomenalisation.